Faktor-Faktor Motivasi dalam Discovery Learning Studi Kualitatif Pada Pembelajar Bahasa Arab - Masruroh, Anifa; Hizmatul Himmah, Ro’fat (Cetta: Jurnal Ilmu Pendidikan, 2025)
The Arabic language learning at MTs N 5 Banyuwangi still employs conventional methods that are less engaging, leading to low student motivation in learning. This study aims to analyze various motivational factors that contribute to students' success in learning Arabic. The main focus of this research is the implementation of the discovery learning approach to understand how intrinsic and extrinsic motivation can support the learning process. This study utilizes a qualitative method to achieve the established objectives. Data collection was conducted through in-depth interviews to gain a more detailed understanding of students' experiences and motivation in learning Arabic. The research findings indicate that the implementation of discovery learning can enhance students' intrinsic and extrinsic motivation by providing a more active, exploratory, and enjoyable learning experience. However, some challenges were identified, such as limited vocabulary and difficulties in independently understanding concepts. Factors supporting students' success include learning interest, a conducive learning environment, teacher creativity, and the use of interactive media. The conclusion of this study suggests that discovery learning is an effective strategy for improving motivation and Arabic learning outcomes. This method encourages students to be more active and independent in exploring learning materials. However, its effectiveness highly depends on optimal teacher guidance and a supportive learning environment, including peer support and the use of interactive learning media.